P, C-Chelation versus P, P-coordination of unsymmetrical phosphorus ylides in palladacyclopropa[60]fullerene complexes; synthetic, spectroscopic, and theoretical studies. Issue 35 (15th August 2016) - Sabounchei, Seyyed Javad; Hosseinzadeh, Marjan; Hashemi, Ali; Salehzadeh, Sadegh; Maleki, Farahnaz
Abstract : New palladacyclopropa[60]fullerene complexes containing P, C-chelated and P, P-coordinated unsymmetrical phosphorus ylides were synthesized and characterized successfully. Abstract : The new palladacyclopropa[60]fullerene complexes incorporating α-keto stabilized phosphorus ylides were synthesized in a three-component reaction of the unsymmetrical phosphorus ylides [Ph2 P(CH2 ) n PPh2 C(H)C(O)C6 H4 - m -R] ( n = 1, R = Br, NO2, (Y 1, Y 2 ); n = 2, R = Br, NO2, (Y 3, Y 4 )), C60 and Pd(dba)2 (dba = dibenzylideneacetone). The obtained novel P, C-chelated [(η 2 -C60 )Pd(κ 2 -Y 1 )] (1 ) and [(η 2 -C60 )Pd(κ 2 -Y 2 )] (2 ) complexes and P, P-coordinated [(η 2 -C60 )Pd(Y 3 )2 ] (3 ) and [(η 2 -C60 )Pd(Y 4 )2 ] (4 ) complexes were characterized successfully by IR, UV-Vis, ESI-MS and NMR ( 1 H, 13 C and 31 P) spectroscopic methods. Complexes1–4 are rare examples of palladacyclopropa[60]fullerene complexes with phosphorus ylide ligands. Spectroscopic results revealed that none of possible side products including P, P-coordinated [(η 2 -C60 )Pd(Y 1 )2 ] and [(η 2 -C60 )Pd(Y 2 )2 ] complexes and also P, C-chelated [(η 2 -C60 )Pd(κ 2 -Y 3 )] and [(η 2 -C60 )Pd(κ 2 -Y 4 )] complexes are formed. The EDA analysis indicated that in all the above complexes the metal–ligand bonds are mostly electrostatic in nature.